2012
DOI: 10.1111/j.1439-0396.2012.01317.x
|View full text |Cite
|
Sign up to set email alerts
|

Capability of different non‐nutritive feed additives on improving productive and physiological traits of broiler chicks fed diets with or without aflatoxin during the first 3 weeks of life

Abstract: An experiment was conducted to determine whether some non-nutritive feed additives (NNFA) could block the adverse effects of aflatoxin (AF) on growth performance and physiological parameters of Cobb broilers throughout the period from 1 to 21 day of age. There were eight treatments consisting of two levels of AF at 0 and 200 ppb and four NNFA within each AF level. These additives included mannan oligosaccharides (MOS) at 2 g/kg diet, hydrated sodium calcium aluminosilicate (HSCAS) at 2 g/kg diet and Lactobacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 28 publications
1
25
0
1
Order By: Relevance
“…Increased lipid peroxidation in the erythrocytes leads to erythrocytic burst with a concomitant increase in hemolysis; hence, this could account for the low PCV and hemoglobin level observed in this study. Previous studies have shown that AFB1 decreased the PCV and hemoglobin of rabbits ( 41 ) and broiler chicks ( 42 ). Huang et al .…”
Section: Discussionmentioning
confidence: 97%
“…Increased lipid peroxidation in the erythrocytes leads to erythrocytic burst with a concomitant increase in hemolysis; hence, this could account for the low PCV and hemoglobin level observed in this study. Previous studies have shown that AFB1 decreased the PCV and hemoglobin of rabbits ( 41 ) and broiler chicks ( 42 ). Huang et al .…”
Section: Discussionmentioning
confidence: 97%
“…There are also some reports that organic TBs such as live yeast (Saccharomyces cerevisiae), gluco-mannan, mannanoligo-saccharide are effective in binding of AFB1 in feed at feeding trials performed in vivo. It was mentioned that the adverse effects of AFB1 were reduced by the addition of feed glucomannan (Karaman et al, 2005;Uttpatel et al, 2011) and mannanoligo-saccharide (Attia et al, 2013) in in vivo feeding trials. Live yeast strains were found to be efficient in binding of AF after mixing as a feed additive (Dogi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, compared with sows from L-THI, sows from H-THI had lesser individual piglet birth weight (P < 0.10). It's reported that dietary supplementation of non-nutritive feed additives improved productive and physiological parameters of livestock (28,29). However, dietary supplementation of SCFP did not affect reproductive performance of sows.…”
Section: Reproductive Performancementioning
confidence: 98%